Reward Functions to Reinforce a Goal-Based Management Process - Peters, Donald H. (Management Science, 1972)
A mathematical model for an incentive system is presented for use within an organization which has a single criterion measure and which sets goals for performance in advance. This model is examined and assumptions stated concerning what restrictions are necessary to reinforce “desired” behavior. With this general model a series of specific examples is derived and evaluated. The implementation of the most obviously practicable example is discussed. Directions for research with such incentives are suggested.